2018
DOI: 10.1002/brb3.995
|View full text |Cite
|
Sign up to set email alerts
|

Ceruloplasmin in Parkinson's disease and the nonmotor symptoms

Abstract: ObjectivesTo investigate the relationship between ceruloplasmin (CP) and Parkinson's disease (PD), and the correlation between CP level and the time difference between nonmotor symptoms and motor symptoms and the diagnosis were also mentioned.Materials and MethodsSixty‐six patients diagnosed with PD for the first time were included in the study. They were divided into CP reduction group (31 cases) and CP normal group (35 cases) according to their CP level. The estimated time difference between nonmotor symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Moreover, other authors suggested that heterozygous mutations in PLA2G6 may also contribute to the susceptibility for developing PD (Ferese et al, 2018), as some PLA2G6 heterozygous mutations were presented in PD patients (Bower et al, 2011; Lu et al, 2012). We assume that the I898M damaging mutation in the CP gene, which plays an important role in the iron and copper metabolism in the brain (Zhao et al, 2018), could intensify the risk of developing PD. These four patients in Table 5 with a mean AOO (42 ± 5.72 years) is rather like the sporadic patients with a single genetic risk variant presented in Table 3 with a mean AAO (40 ± 6.94 years) than the sporadic patients with potential oligogenic background (presented in Table 4 with a mean AOO 34.5 ± 4.95 years).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other authors suggested that heterozygous mutations in PLA2G6 may also contribute to the susceptibility for developing PD (Ferese et al, 2018), as some PLA2G6 heterozygous mutations were presented in PD patients (Bower et al, 2011; Lu et al, 2012). We assume that the I898M damaging mutation in the CP gene, which plays an important role in the iron and copper metabolism in the brain (Zhao et al, 2018), could intensify the risk of developing PD. These four patients in Table 5 with a mean AOO (42 ± 5.72 years) is rather like the sporadic patients with a single genetic risk variant presented in Table 3 with a mean AAO (40 ± 6.94 years) than the sporadic patients with potential oligogenic background (presented in Table 4 with a mean AOO 34.5 ± 4.95 years).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, APP expression is decreased in the SN of PD patients, leading to a similar iron-associated phenotype as APP knockout mice 66,68 . Furthermore, the ferroxidase activity of CP required to facilitate iron efflux through FPN is decreased in both patients and animal models of PD 108,109 . Further support for iron elevation as a cause of parkinsonian pathology comes from the genetic disorder aceruloplasminemia, in which CP is mutated, often leading to a parkinsonian phenotype including gait difficulties, ataxia, involuntary movements and cognitive decline that correlate with brain iron deposition 110,111 .…”
Section: The Role Of Iron In Pd Pathologymentioning
confidence: 99%
“…There have been reports linking lower CP levels with PD development, and CP gene mutations have been associated with substantia nigra hyperechogenicity using transcranial sonography. 38 Additionally, hyperechogenicity is a common finding in idiopathic PD patients and many studies suggest that it is an important risk marker of future PD . 39,40 One mutation associated with SN hyperechogenicity is p.R793H.…”
Section: Cpmentioning
confidence: 99%